need to solve this problem in steps 5(2x+6)=-4(-5-2x)+3x

Question

need to solve this problem in steps 5(2x+6)=-4(-5-2x)+3x

in progress 0
19 mins 2021-09-15T02:09:29+00:00 1 Answer 0

Simplifying

5(2x + 6) = -4(-5 + -2x) + 3x

Reorder the terms:

5(6 + 2x) = -4(-5 + -2x) + 3x

(6 * 5 + 2x * 5) = -4(-5 + -2x) + 3x

(30 + 10x) = -4(-5 + -2x) + 3x

30 + 10x = (-5 * -4 + -2x * -4) + 3x

30 + 10x = (20 + 8x) + 3x

Combine like terms: 8x + 3x = 11x

30 + 10x = 20 + 11x

Solving

30 + 10x = 20 + 11x

Solving for variable ‘x’.

Move all terms containing x to the left, all other terms to the right.

Add ‘-11x’ to each side of the equation.

30 + 10x + -11x = 20 + 11x + -11x

Combine like terms: 10x + -11x = -1x

30 + -1x = 20 + 11x + -11x

Combine like terms: 11x + -11x = 0

30 + -1x = 20 + 0

30 + -1x = 20

Add ‘-30’ to each side of the equation.

30 + -30 + -1x = 20 + -30

Combine like terms: 30 + -30 = 0

0 + -1x = 20 + -30

-1x = 20 + -30

Combine like terms: 20 + -30 = -10

-1x = -10

Divide each side by ‘-1’.

x = 10

Simplifying

x = 10